Expenditure Components of GDP (2000-2018): The Case of India, China and USA - Aditya Desai, Namrata Sandhu (International Journal of Advanced Science and Technology, 2020)
With the aim to examine how the economy functions and changes over time, this study graphs trends in the main expenditure components of the gross domestic products of three countries: India, China and United Sates of America. With the help of eighteen-year time series data (2000-2018), this study also attempts an inter-country comparison of these trends. Data related to four expenditure components of GDP: household consumption, investment expenditure, government spending and net exports is examined in this study. This data are critically analyzed and policy implications are discussed from a developmental perspective.